Smart Synthesis of High-Performance Thermosets Based on ortho-Amide–Imide Functional Benzoxazines - Zhang, Kan; Ishida, Hatsuo (Frontiers in Materials, 2015)
High-performance thermosets via amide–imide functional benzoxazine resins as precursors have been synthesized. The structures of synthesized monomers have been confirmed by 1H NMR and Fourier transform infrared. Among these two benzoxazine monomers, the ortho-amide–imide functional benzoxazine resin shows powerful features both in the synthesis of benzoxazine monomers and the properties of the corresponding thermosets. For the cross-linked poly(amide-co-imide) based on ortho-amide–imide functional benzoxazine, a smart route is adopted to develop a more thermally stable cross-linked poly(benzoxazole-co-imide). Besides, the poly(benzoxazole-co-imide) can also undergo a further thermal treatment to form polybenzoxazole. Furthermore, a main-chain type ortho-functional polybenzoxazine with amide-co-imide and benzoxazine groups as repeating units has also been prepared. Both the ortho-amide–imide functional benzoxazine and main-chain type polybenzoxazine resins show the possibility to form high-performance thermosets with low cost and easy processability.